A longitudinal study of clinical and immunological findings in 52 patients with relapsing retinal vasculitis. Issue 6 (June 1988) - Stanford, M R; Graham, E; Kasp, E; Sanders, M D; Dumonde, D C
Abstract : Fifty-two patients with retinal vasculitis–26 with idiopathic disease and 26 with associated systemic inflammatory disease–were followed up for periods ranging from six months to 12 years. The aim of the study was to determine the relationship between relapse of uveitis, visual outcome, and the occurrence of circulating immune complexes (CIC) and antiretinal antibodies. In a total of 69 relapses, CIC were increased in one-third of patients and antiretinal antibodies in one-half. In those 34 patients who expressed antiretinal antibodies 27 (79%) of the relapses were characterised by antiretinal antibodies in the absence of raised CIC levels (p less than 0.01). These findings support our previous hypothesis that CIC may have a protective role in autoimmune retinal vasculitis and that antiretinal autoimmunity is of pathogenetic importance in relapse. In individual patients the visual outcome was not related to the number of relapses or to the CIC-autoantibody pattern, suggesting the operation of additional features which merit identification.